Analisis Strategi Marketing Pasar Dalam Meningkatkan Penjualan Digital Printing Pada PT Prabu Hassa Prima Ditinjau Dalam Perspektif Islam - Asfia Ziani; Miftahudin (DPPM Universitas Pelita Bangsa, 2024)
PT Prabu Hassa Prima, a Digital Printing company that has experienced a significant transformation since its inception in 2012. In an era of rapid development of the digital printing industry, this company stands out as a major player with an innovative focus. This research is interested in analyzing the market marketing strategy at PT Prabu Hassa Prima in an effort to increase digital printing sales, with an emphasis on Islamic principles. This research uses a qualitative descriptive approach with case studies, data was collected through in-depth interviews, observations and document studies. Data analysis techniques for data reduction, data presentation and conclusions. The results of this research show that PT Prabu Hassa Prima is quite successful in implementing a Market Marketing strategy, namely a market coverage strategy by serving the entire market spectrum with a focus on a multi-market strategy. geographic strategy focused on the local market in the city of Bandung. Meanwhile, the market entry strategy is adapting as a strategy to compete in the market, with regular updates to the e-commerce website and digital marketing platform. Then PT Prabu Hassa Prima has adhered to Islamic principles, with the characteristics of Amanah, fathonah. Fair pricing and show responsibility.